The Difference of Barthel Index Score Based on Stroke Severity, Weakness Side, and Onset of Physiotherapy in Ischemic Stroke Patients at Atma Jaya Hospital - Agustina Novita Putri Soegiarto; Linda Suryakusuma; Jane Pelealu (Indonesian Journal of Physical Medicine & Rehabilitation, 2017)
Background: Stroke is the third cause of disability that can affect the Activity of Daily Living (ADL). Ischemicstroke had higher incidence compared to hemorrhagic strokes. Rehabilitation in the form of physiotherapy canreduce the level of ADL dependencies, that is be measured by Barthel Index Score. Stroke severity, weaknessside, and physiotherapy onset can be factors that influence the success of physiotherapy to reducing the levelof ADL dependencies.Methods:A descriptive analytic study with a cross-sectional design in ischemic stroke patients using secondarydata from the Stroke Registry and medical records at Atma Jaya Hospital for the period of January 2016 toDecember 2017. The data were analyzed using Chi-Square.Results: Study on 110 subjects, consisted of 62 men(56.4%), aged divided by under of 58 years, and above of 58years were 52(47.3%) and 58 (52.7%). While subjects divided by stroke severity, i.e. minor, moderate, moderateto severe, and severe; 44 (40%), 58 (52.7%), 5 (4.5%), and 3 (2.7%) respectively. There were 77 participants(70%) had right side weakness and 33 participants (30%) were left side weakness. The changes of Barthel Indexof ADL score, were 73 (66.4%) improvement, 6 (5.5%) deterioration, and 31 (28.2%) remained. The study hasshown relationship between severity of stroke (p=0.008), weakness side (p=0.000), and physiotherapy onset(p=0.039) with the changes of Barthel Indexscore after treatment.Conclusion: There was a relationship between stroke severity, the weakness side of stroke, and physiotherapyonset with the better result of Barthel Index of ADL score after the physiotherapy.Keywords: Activity of Daily Living (ADL), Barthel Index, ischemic stroke, physiotherapy onset, stroke severity,Weakness side